Sailing the Indian Ocean in Ancient Times - Jean-Marie Kowalski (Angles)
Navigations in the Indian Ocean, well attested in the ancient periplographical and geographical literature, pose a series of questions to the historian. These investigations are more often than not fragmentary and provide information only on some of the desired data. Nor can they attest the existence of cartographic representations. However, whether they are Greek or Latin, many navigators had experienced what is was to sail in the Indian Ocean at that time, offering a constantly evolving representation of this area.